A new subgenus and two new species of Zercon C. L. Koch, 1836 (Acari: Zerconidae) from Southeast Asia - Ujvári, Zsolt (Zootaxa, 2011)
Two new species, Zercon (Zercorientalia) formosianus sp. nov. and Zercon (Zercorientalia) spinosus sp. nov., are described from the high mountain zone of Taiwan. A new subgenus, Zercon (Zercorientalia) subgen. nov., is established for these species, on the basis of a unique combination of podonotal chaetotaxy and pore positions. Zercon (Zercorientalia) sinensis Petrova & Taskaeva, 1968 is transferred from Zercon (Zercon) Koch, 1836 to the new subgenus. The taxonomic relevance of podonotal chaetotaxy is discussed.